2004
DOI: 10.1055/s-2004-815525
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine in the Treatment of Obsessive-compulsive Symptoms in Schizophrenia Patients: A Case Series Study

Abstract: Further controlled investigations in a larger cohort of OC schizophrenic patients are needed to substantiate our hypothesis. OCD:Obsessive-compulsive disorder OCS:Obsessive-compulsive symptoms SRI:Serotonin reuptake inhibitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…In addition to the association with duration of treatment, a positive correlation between dose or serum levels of CLZ and severity of OCS has been reported in independent samples [3,41,63]. In line with these previous results, we found positive correlations between the daily dose of CLZ and OCS severity [62].…”
Section: Influence Of Treatment Dose and Blood Serum Levels Of Clz Onsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to the association with duration of treatment, a positive correlation between dose or serum levels of CLZ and severity of OCS has been reported in independent samples [3,41,63]. In line with these previous results, we found positive correlations between the daily dose of CLZ and OCS severity [62].…”
Section: Influence Of Treatment Dose and Blood Serum Levels Of Clz Onsupporting
confidence: 91%
“…In addition, the substance embarks important protective effects against suicidal behaviour resulting in lowest mortality of schizophrenics as documented in the large, naturalistic FIN11-study [48]. However, the de novo occurrence or exacerbation of OCS has most often been observed during treatment with CLZ [39,41] and several epidemiological and pharmacological arguments support the attribution of pro-obsessive effects.This review aims at summarizing the evidence for OCS-induction by CLZ in order to provide a basis for pathogenetic considerations and the design of further clinical trials. For this task, we systematically screened medical databases (Medline OVID, PSYNDEX and PsycINFO) for publications until June 2011 using the keywords (“schizophrenia” or “Psychosis” or “psychotic disorder”) linked with (“OCD” or “obsessive” or “compulsive”).…”
Section: Second-onset Ocs Induced By Antiserotonergic Antipsychoticsmentioning
confidence: 99%
“…Since then several studies show a clear association and possible causal interaction between SGA-treatment, most importantly CLZ (Schirmbeck and Zink, 2012), and the de novo occurrence of OCS (de Haan et al, 2004; Reznik et al, 2004; Kwon et al, 2009b; Schirmbeck et al, 2011). …”
Section: Ocs Induced By Second-generation Antipsychoticsmentioning
confidence: 99%
“…In addition, the substance demonstrates important anti-suicidal effects resulting in low mortality rates of CLZ-treated schizophrenia patients (Tiihonen et al, 2009). However, within a variety of other important side effects (Asenjo Lobos et al, 2010), the de novo occurrence or exacerbation of OCS under antipsychotic treatment has most often been observed with CLZ (Lykouras et al, 2003; Reznik et al, 2004; Schirmbeck and Zink, 2012). Due to a lack of controlled clinical trials, proposed causal interrelations cannot be confirmed, according to the general criteria suggested by Bradford Hill (2011).…”
Section: Ocs Induced By Second-generation Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation